Biological and phytochemical analysis of fractionated extracts of Ziziphus nummularia against pathogenic bacteria, oxidative stress and cytotoxicity - Sehrish IMRAN; Yamin BIBI; Abdul QAYYUM; Sobia NISA; Raheem SHAHZAD; Sulaiman A. ALHARBI; Mohammad J. ANSARI (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2024)
In modern medicine, synthetic drugs are predominant, yet they often pose health hazards. So, there is a need to find natural alternatives. Ziziphus nummularia (Burm. F.) Wight & Arn., belongs to family Rhamnaceae, is well known for its traditional value such as its fruits have been used as natural appetizer and orally consumed around the world. This study investigated the phytochemical composition and bioactivity of crude and fractionated extracts from the stem bark of Ziziphus nummularia. Crude extracts were prepared using cold maceration, followed by partitioning based on polarity into n-hexane, chloroform, and ethyl acetate fractions. These extracts were subjected to phytochemical analysis and evaluated for antioxidant, antibacterial, and cytotoxic activities. The crude methanolic extract exhibited the highest antioxidant activity, with IC50 values of 136.49 μg/mL in DPPH and 78.9 μg/mL in ABTS assays. Antibacterial tests using the agar well diffusion method revealed that the methanolic extract, ethyl acetate, and chloroform fractions demonstrated broad-spectrum antibacterial activity against E. coli, K. pneumoniae, S. aureus, and S. epidermidis, with inhibition zones ranging from 0 to 8.43 ± 0.23 mm at 400 mg/mL. The brine shrimp lethality assay indicated significant cytotoxicity in the methanolic, ethyl acetate, and chloroform extracts, compared to the negligible effect of the n-hexane fraction. These findings highlight the potential of Z. nummularia as a source of bioactive compounds with therapeutic applications against infectious diseases, toxins, and oxidative stress. Further isolation of pure compounds and animal trials are recommended to explore its potential in drug discovery.